A randomised, double-blind, four-way, crossover trial comparing the 24-h FEV1 profile for once-daily versus twice-daily treatment with olodaterol, a novel long-acting β2-agonist, in patients with chronic obstructive pulmonary disease. Issue 5 (May 2015) - Joos, Guy F.; Aumann, Joseph-Leon; Coeck, Carl; Korducki, Lawrence; Hamilton, Alan L.; Kunz, Christina; Aalbers, René
Summary Background This randomised, double-blind, four-way, crossover, Phase II study compared the 24-h forced expiratory volume in 1 s (FEV1) profile of alternative dosing frequencies of two total daily doses of olodaterol (5 and 10 μg) in patients with chronic obstructive pulmonary disease (COPD). Methods Patients received olodaterol 2 μg twice daily (BID), 5 μg BID, 5 μg once daily (QD) and 10 μg QD in a randomised sequence over 3-week treatment periods. Co-primary end points were FEV1 area under the curve from 0 to 12 h (AUC0–12) and area under the curve from 12 to 24 h (AUC12–24) responses. Additional lung-function responses, pharmacokinetics and safety were assessed. Results 47 patients were treated. All olodaterol doses provided significant increases in FEV1 versus baseline (p < 0.001) and FEV1 time profiles were nearly identical for olodaterol 5 and 10 μg QD. Olodaterol 5 μg QD demonstrated improved FEV1 AUC0–12 and similar AUC12–24 versus 2 μg BID. Olodaterol 5 μg QD showed slightly increased FEV1 AUC0–12 but lower AUC12–24 compared to 5 μg BID. Bronchodilation over 24 h was similar for olodaterol 5 μg QD and BID. All doses were well tolerated. Conclusions Olodaterol 5 μg QD is efficacious in COPD, with a superior bronchodilatory profile compared to 2 μg BID, which is close to the same total daily dose, and a similar degree of bronchodilation over 24 h compared with double the daily dose (administered as 10 μg QD or 5 μg BID). Trial registration ClinicalTrials.gov: NCT00846768.